2021
DOI: 10.1002/app.50782
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of 3D printing parameters for high‐performance biodegradable materials

Abstract: Developing 3D printing high‐performance biodegradable materials is important to protect the environment and deal with emergencies such as COVID‐19. Fused deposition modeling (FDM), one of the 3D printing methods, has many advantages, such as low cost and wide range of materials. However, the weak interlayer adhesion is an important factor restricting the development of FDM. In addition to the influence of material properties, the optimization of 3D printing parameters is also an important means to give full pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 37 publications
0
19
0
Order By: Relevance
“…The improvement of mechanical properties of PLA attained by blending with PBAT or PBSA, as well by addition of nanofillers, pushed development of these materials as filaments for 3D printing. PLA/PBAT and PLA/PBSA blends were investigated by a number of researchers, to test their suitability as 3D printing material, either as binary blends, or as compatibilized formulations [181][182][183][184], as well as containing micro-and nanofillers [185][186][187].…”
Section: Applications Of Pla/pbsa and Pla/pbat Blends And Nanocompositesmentioning
confidence: 99%
“…The improvement of mechanical properties of PLA attained by blending with PBAT or PBSA, as well by addition of nanofillers, pushed development of these materials as filaments for 3D printing. PLA/PBAT and PLA/PBSA blends were investigated by a number of researchers, to test their suitability as 3D printing material, either as binary blends, or as compatibilized formulations [181][182][183][184], as well as containing micro-and nanofillers [185][186][187].…”
Section: Applications Of Pla/pbsa and Pla/pbat Blends And Nanocompositesmentioning
confidence: 99%
“…Lyu et al. [ 57 ] investigated the effect of 3D printing parameters such as layer thickness, nozzle temperature, printing speed, and platform temperature using an orthogonal experimental design. The results showed that when the layer thickness was 0.15 mm, the printing speed was 50 mm/s, the nozzle temperature was 200 °C., and the platform temperature was 50 °C., the 3D printing specimen operated optimally.…”
Section: The Fdm Printing Parametermentioning
confidence: 99%
“…[ 56 ] PLA Nozzle temperature = 215 °C Tensile strength Layer thickness = 0.4 mm Stiffnes Bed temperature = 55 °C Elastic modulus Printing speeds = 20 mm/s Raster orientations = 0° Lyu et al. [ 57 ] PLA Layer thickness = 0.15 mm Yield strength Printing speed = 50 mm/s Elongation at break Nozzle temperature = 200 °C Dimensional accuracy Platform temperature = 50 °C Deomore and Raykar [ 58 ] PLA Layer thickness = 0.3 mm Time Speed = 100 mm/h Weight of Product In fill percentage = 55% Filament length Samykano [ 59 ] PLA Layer height = 0.3 mm Ultimate tensile strength Raster angle = 40 °C Fracture strain Infill density = 80% Elastic modulus Yield strength Toughness Hikmat, Rostam, and Ahmed [ 60 ] PLA Build orientation = on-edge Tensile strength Raster orientation = 30/-60° Nozzle diameter = 0.5 mm Extruder temperature = 220 °C Infill density = 100% Extruding speed = 20 mm/s Fard et al. [ 61 ] PCL Nozzle temperature = 100 °C Structural integrity Print speed = 15 mm/s Compressive strength Build plate temperature = 30 °C Fan speed = 100% Ariadna et al.…”
Section: The Fdm Printing Parametermentioning
confidence: 99%
“…The most common polymers used in FFF are thermoplastics, such as polylactic acid (PLA), 9,10 polyamides (PA), 11,12 acrylonitrile butadiene styrene (ABS) 13,14 and polyetheretherketone (PEEK) 15,16 et al However, polyesters such as polyethylene terephthalate (PET), one of the most widely used thermoplastics, are rarely used for FFF. This is because polyester cannot cool and solidify rapidly during the printing process, and the strong fluidity will cause the sample to collapse and fail to form, which is determined by its crystallinity 17 .…”
Section: Introductionmentioning
confidence: 99%